Pengaruh Self Efficacy, Interaksi Sosial Terhadap Minat Berwirausaha dimoderasi Karakteristik Kewirausahaan Peserta Didik - Aieny, Fauzia; Ahman, Eeng; Machmud, Amir; Kurjono, Kurjono (Universitas Pendidikan Ganesha, 2020)
This study aims to determine and analyze the effect of self-efficacy, social interaction on entrepreneurial interest which is moderated by the entrepreneurial characteristics of students. The method used in this study was an explanatory survey research with data collection techniques through questionnaires and observations. The population of this study is 400 students of Senior High School 1 Subang class XI for the 2020/2021 academic year with a sample of 100 students by using simple random sampling techinuques. The collected data were then analyzed using descriptive analysis techniques and multiple linear regression with Moderate Regression Analysis (MRA). The collected data were then analyzed using descriptive analysis techniques and multiple linear regression with Moderate Regression Analysis (MRA). The results showed 1) the level of interest in entrepreneurship, self-efficacy, social interaction and entrepreneurial characteristics of students were in the medium category. 2) self-efficacy had a positive and significant effect on interest in entrepreneurship. 3) social interaction had a positive and significant effect on interest in entrepreneurship. 4) the entrepreneurial characteristics of the participants moderate the effect of self-efficacy on interest in entrepreneurship. 5) entrepreneurial characteristics did not moderate the effect of social interaction on interest in entrepreneurship.